Direct synthesis of quinazolinones via the carbon-supported acid-catalyzed cascade reaction of isatoic anhydrides with amides and aldehydes. (2nd March 2021) - Zhang, Xiangyu; Luo, Chujun; Chen, Xiaoyong; Ma, Weilin; Li, Bin; Lin, Zirui; Chen, Xiuwen; Li, Yibiao; Xie, Feng
Graphical abstract: Highlights: Novel and green catalytic system for the construction of quinazolinones with reusable carbon-supported acid. Broad substrate scope, excellent functional tolerance, and using air as the sole oxidant. Selective hydrosilylation of quinazolinones without reduction of CN bond. Abstract: A novel catalytic system is reported for the construction of quinazolinones via the carbon-supported acid-catalyzed cascade coupling of isatoic anhydrides with amides and aldehydes. Subsequent selective hydrosilylation of the quinazolinones using a hydrogen-transfer strategy was also explored to provide dihydroquinazolines with structural diversity. The developed methodology proceeds with a broad substrate scope, excellent functional group tolerance, and utilizes a reusable catalyst and air as a green oxidant.